2021
DOI: 10.3389/fcell.2021.774989
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum-Mitochondria Contacts: A Potential Therapy Target for Cardiovascular Remodeling-Associated Diseases

Abstract: Cardiovascular remodeling occurs in cardiomyocytes, collagen meshes, and vascular beds in the progress of cardiac insufficiency caused by a variety of cardiac diseases such as chronic ischemic heart disease, chronic overload heart disease, myocarditis, and myocardial infarction. The morphological changes that occur as a result of remodeling are the critical pathological basis for the occurrence and development of serious diseases and also determine morbidity and mortality. Therefore, the inhibition of remodeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 281 publications
(337 reference statements)
0
18
0
1
Order By: Relevance
“…Cytosolic overload has been previously associated with an increase in Na + /Ca 2+ exchanger (NCX1) expression, which is encoded by HIF-1 [ 59 ] and known to predispose to ROS-mediated myocardial injury [ 60 ]. Finally, cytosolic Ca 2+ overloading contributes to Serca2a activation by phospholamban phosphorylation that could explain Ca 2+ rapid accumulation in ER and subsequent ER stress [ 61 ]. Otherwise, it has been demonstrated that HIF-1α overexpression promotes PLB phosphorylation and alters Ca 2+ handling [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cytosolic overload has been previously associated with an increase in Na + /Ca 2+ exchanger (NCX1) expression, which is encoded by HIF-1 [ 59 ] and known to predispose to ROS-mediated myocardial injury [ 60 ]. Finally, cytosolic Ca 2+ overloading contributes to Serca2a activation by phospholamban phosphorylation that could explain Ca 2+ rapid accumulation in ER and subsequent ER stress [ 61 ]. Otherwise, it has been demonstrated that HIF-1α overexpression promotes PLB phosphorylation and alters Ca 2+ handling [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Next, we studied the mechanism by which LBP protects skin cells against PM2.5-induced apoptosis and cytotoxicity. The ER is the main place for protein processing and folding in the cell, and it is the largest Ca 2+ storage organelle in the cell [ 36 ]. When cells are stressed by external factors, the ER stress response will be activated, which may cause Ca 2+ imbalance [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…After an index event, misfolded proteins are accumulated in the ER promoting the activation of the unfolded protein response in order to maintain proteostasis. In the case of failure of the misfolded protein repair, or of a large amount of accumulated unfolded proteins, a vicious circle begins [ 62 , 63 ]. This vicious circle is characterized by the loss of homeostatic capacity, promoting apoptosis.…”
Section: Inflammationmentioning
confidence: 99%